Information technology capabilities : a bibliometric vision of the conceptual and intellectual structures and the past and future research directions - Marchiori, Danilo Magno; Rodrigues; Ricardo José de Ascensão Gouveia; Mainardes, Emerson Wagner; Popadiuk, Silvio (Emerald, 2025)
Purpose
Scientific production on the topic of information technology (IT) capabilities grows each year, leading researchers working in the field into difficulties to keep abreast of the new research flows, as well as to know the intellectual and conceptual structures that sustain the area. Thus, this study aims to present the result of the application of a quantitative approach on the international scientific production on the subject.
Design/methodology/approach
Several complementary bibliometric techniques were combined, such as keywords co-occurrence, bibliographic coupling and cocitation analysis. Considering that the bibliometric research support software currently available to the academic community has strengths and weaknesses, the present study uses three recent tools of analysis (VOSviewer, SciMAT and Bibliometrix), to explore the best that each can offer.
Findings
The authors analyzed 219 scientific papers available on the Web of Science. The authors identify the origins of the current literature on IT capabilities, as well as its foundations and main intellectual and conceptual structures, including a longitudinal view of the development of the theme. The paper also presents the main research fronts in the field, as well as several opportunities that can contribute to the advancement of research involving IT capabilities.
Originality/value
The fundamental themes for structuring the whole of the scientific production on IT capabilities, which had a higher level of development and connection with external research flows, are organizational performance, strategic management, resource and value-based view. Thus, future researchers will find underlying literature on IT capabilities in the context of business a rich and varied literature involving these major themes.